The majority rule principle in political leadership and decision-making: An Islamic perspective - Shuriye, Abdi Omar (Institute of Islamic Understanding Malaysia, 2002)
One of the most complex political issues in today's world politics is ethnicity. As nations struggle for harmonious political system, ethnic politics seem bothering. In fact developed nations face internal ethnic-based conflicts. A comprehensive method is needed as ethnic diversity of a variety of societies is increasingly becoming prominent in world politics. The post-cold war era is an era where ethnic nationalism has become the major source of intrasocietal conflicts. In Muslim political thought, this area of study has yet to be academically evaluated from the Quranic point of view, as Muslim political thinkers have adopted the Western systems in political administration. In fact a vast number of Muslim thinkers opine that majority rule principle originated from the Western democratic systems. Contrary to this assertion however, the two most authentic sources of Islam - the Qur'an and the Sunnah - made direct reference to the principle of majority rule. The four rightly guided Caliphs also ruled according to this principle. Nonetheless, differences of opinion among governmental bodies, ethnic groups and individuals in any nation or society, more often than not, preclude unanimity in decision-making, particularly in the Muslim world. Although motives of decision-makers and societal leaders in acting one way or another are far too complex, experience suggests two reasons as the primary causes for the lack of unanimity in collective decision-making and mutual unity among leaders. One of these reasons is the general selfish tendency of man. And the other is the diverse and varying perceptions towards the common good. This is so because the political management in any society involves the adjustment of conflicting interests and opposing claims of man's selfishness that would assert his viewpoint and personal interest in any process of policy-making. In fact in today’s political environment respect for ethical goals of life do not seem to be the rule of politics but the exception. In Islamic political thought, at least on the theoretical level, the Divine Will (The Shari'ah) makes respect for moral and ethical goals on the part of Muslim individuals as well as on all governmental bodies a matter of both constitutional and religious obligation. It would nonetheless be a staid mistake to assume that the moral ideals of the Divine Will could prevail over selfish tendencies of man at all times. The issue of majority rule from the Islamic perspective has its roots in early Islamic political thought. Immediately after the demise of Prophet Muhal'nmad, his companions gathered to decide his successor in the political leadership of the society. The result was "majority rules". This paper argues that in any modern society the largest ethnic group must rule politically, in other words majority rule principle should be exercised in order to maintain social, political and religious stability. The paper also insinuates that disputes among leaders and ethnic groups of any given nation can be resolved through the use of the "majority rules principle". With the full implementation of this principle, conflicts between tribes and ethnic groups, sometimes between diverse cultures and belief systems particularly in modern Muslim nations, could be facilitated.